2012
DOI: 10.1007/s10897-012-9483-0
|View full text |Cite
|
Sign up to set email alerts
|

Risky Business: Risk Perception and the Use of Medical Services among Customers of DTC Personal Genetic Testing

Abstract: Direct-to-consumer genetic testing has generated speculation about how customers will interpret results and how these interpretations will influence healthcare use and behavior; however, few empirical data on these topics exist. We conducted an online survey of DTC customers of 23andMe, deCODEme, and Navigenics to begin to address these questions. Random samples of U.S. DTC customers were invited to participate. Survey topics included demographics, perceptions of two sample DTC results, and health behaviors fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
180
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(203 citation statements)
references
References 35 publications
(46 reference statements)
18
180
3
Order By: Relevance
“…African Americans are represented more highly in our sample than the general US population (12.6 % per US Census website) and participants generally had lower education levels than other studies of DTCGT (Bloss et al 2011;Kaufman et al 2012;McGowan et al 2010;O'Daniel et al 2010). Recruiting from an urban primary care office may have contributed to a more diverse sample than other early studies of this testing, including those of early users (Kaufman et al 2012;McGowan et al 2010). Our participants were not early users or adopters, as none had taken a DTC genetic test prior to the study.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…African Americans are represented more highly in our sample than the general US population (12.6 % per US Census website) and participants generally had lower education levels than other studies of DTCGT (Bloss et al 2011;Kaufman et al 2012;McGowan et al 2010;O'Daniel et al 2010). Recruiting from an urban primary care office may have contributed to a more diverse sample than other early studies of this testing, including those of early users (Kaufman et al 2012;McGowan et al 2010). Our participants were not early users or adopters, as none had taken a DTC genetic test prior to the study.…”
Section: Discussionmentioning
confidence: 76%
“…Kaufman et al 2012 is one of the few studies to assess the impact of DTCGT on health behaviors of actual users (Kaufman et al 2012). Via an online survey, they explored how consumers interpreted risk information and how their interpretations influenced their healthcare.…”
Section: Introductionmentioning
confidence: 99%
“…There are some examples in the literature investigating the effect of DTC testing on behaviour change (Table 1). Kaufman et al carried out an online survey of DTC customers of 23andMe, deCODEme and Navigenics (19) . A random selection of customers were invited to take part with 33 % completing the survey (n 1048).…”
Section: Studies Investigating the Impact Of Direct-to-consumer Testingmentioning
confidence: 99%
“…Furthermore, a change in health anxiety was reported by 24·6 % of consumers, of which, 85·3 % were a reduction. A major strength of this survey and the one conducted by Kaufman et al (19) was the fact that they were conducted on real-life DTC consumers, rather than those who received the genetic testing free or at a reduced rate. This is in contrast to a study conducted by Bloss et al who recruited employees from health and technology companies who agreed to purchase the Health Compass at a discounted rate (21) .…”
Section: Studies Investigating the Impact Of Direct-to-consumer Testingmentioning
confidence: 99%
“…Meanwhile, there is a growing body of evidence for the effectiveness of tailored feedback in bringing about healthy behaviour change (3)(4)(5)(6) . Surveys of D-T-C services have suggested that they are effective in producing healthy behaviour change in approximately one-third of users (7)(8)(9)(10) . Awareness of D-T-C genetic tests is increasing among consumers (11) .…”
Section: What Is Personalised Nutrition?mentioning
confidence: 99%